Highly efficient and tunable visible-light-catalytic synthesis of 2, 5-diformylfuran using HBr and molecular oxygen. Issue 38 (2nd July 2021) - Hu, Wenwei; She, Jialuo; Fu, Zaihui; Yang, Bo; Zhang, Huanhuan; Jiang, Dabo
Abstract : HBr is a very cheap and efficient bifunctional catalyst for the synthesis of DFF from the photooxidation of HMF by O2 and from the cascade conversion of fructose via a one-step or especially the two-step protocol. Abstract : This paper discloses that inexpensive hydrobromic acid (HBr) is active and highly selective to the photo-oxidation of 5-hydroxymethylfurfural (HMF) to 2, 5-diformylfuran (DFF) with dioxygen (O2 ) or even with water under visible light illumination, which can achieve the highest 89.1% DFF yield in DMSO at 80 °C under pure O2 atmosphere. More importantly, under bifunctional acid-photooxidation catalysis of HBr, fructose can be directly converted to DFF and its two-step cascade conversion in DMSO provides a far higher DFF yield (80.2%) than the one-step cascade conversion in MeCN (42.1%). The results of HMF photooxidation catalyzed by hydrohalic acids, free radical quenching tests and EPR spectrum support that the Br atom and superoxide (O2 − ˙) anion radicals generated by HBr photolysis in O2 are active species for the oxidation of HMF to DFF and their activities are adjusted by the reaction medium. This photo-synthetic protocol is very simple and practical, especially with low operating costs, showing a good industrial application prospect.